Effect of Self-esteem on Perceived Job Insecurity: The Moderating Role of Self-efficacy and Gender - A. Adekiya, Adewale (Naše gospodarstvo/Our economy, 2022)
The high rate of job loss in most crude oil dependent countries, which may be attributed to the recent drop in the price of this commodity in international markets, has intensified the perception of threats associated with potential job loss among the employees who are still employed. Hence, perceived job insecurity, its associated outcome, coupled with how it can be mitigated has become a global phenomenon, which requires the attention of managers and practitioners alike. In this work, we built upon Hobfall’s conservation of resource theory (CRT) to present a research model that links employee’s self-efficacy and gender to the strength or weakness of the relationship between self-esteem and self-perceived job insecurity. Research data were collected from 153 randomly selected Nigerian Bank employees out of 217 drawn from a total population of 509. Based on the results from relevant statistical analysis, it is discovered that, while increase in self-esteem would lead to a significant decrease in job insecurity perception, such significant decrease is, however, not associated with self-efficacy and gender meaning that these variables are not moderators in the self-esteem/perceived job insecurity relationship. In line with these outcomes, we conclude by recommending that managers should focus on developing intervention strategies aimed at improving employee self-esteem with a view of reducing perceived job insecurity. In addition, important areas in need of future research were also identified.